Improving The Students' English Vocabulary By Using Visual Media At The Fourth Year Of SDN 1 Kartasura In 2010/2011 Academic Year - Lewistianto, Ardian; , Dra. Dwi Haryanti, M. Hum; , Dra. Siti Khuzaimah (2013)
This study is aimed to know the students' English vocabulary improvment by using visual media and to describe the achievement of them in the test result. The result of this study hopefully will give contribution in learning English. In this research, visual media are used to improve students' motivation and achievement in learning English. This research was carried out at SDN 1 Kartasura, especially in class 4A that consists of 23 students. To collect the required data, the writer did observation to know the students' motivation and gave test to know academic achievement of students. There were three cycles in this action research in which each cycle used post-test. He analyzed the data by comparing the result of pre-test and post-test. The results of pre-test and post-test were used to know the score of the vocabulary mastery. The mean of the achievement after the teacher did the action was 91.30 that belongs to excellent category. While, before the teacher did the action, the mean of the students achievement was 60 that belongs to poor. Based on the research finding, it can be concluded that (1) visual media can increase the students' motivation in learning English. (2) Visual media can improve the students' English vocabulary in learning English. The students' score was getting better in each cycle. It indicated that the teaching learning process was successful, both the researcher and the students gained the objectives.